Mental Imagery Skills in Competitive Young Athletes and Non-athletes - Di Corrado, Donatella; Guarnera, Maria; Guerrera, Claudia Savia; Maldonato, Nelson Mauro; Di Nuovo, Santo; Castellano, Sabrina; Coco, Marinella (Frontiers in Psychology, 2020)
Mental imagery is a multisensory process that combines as many senses as possible to generate a mental image and process it without the presence of external stimuli. In the sport context, imagery has been described as the condition in which persons imagine themselves while executing skills to deal with the upcoming task or enhance performance. Systematic reviews have shown that imagery improves performance in motor tasks. This study aims at observing not the vividness of image, but the cognitive abilities useful for the generation, inspection, maintenance and manipulation of different categories of images, investigating modifications in mental imagery skills in competitive athletes and non-athletes. Participants were competitive athletes (n=48) and non-athletes (n=48) between the ages of 8 and 13 years (Mage = 10.50, SD = 1.73). The athletes had a minimum of 5 years of practice experience in the sport. They completed the Mental Imagery Test (MIT). Competitive athletes reported higher scores on mental imagery skills than non-athletes. The study contributed to rise the investigation in the particular area of mental imagery, providing an additional support for the multidimensional nature of mental imagery and for its usefulness in in motor and sport sciences.